Detailed Postmortem Profiling of Inflammatory Mediators Expression Revealed Post-inflammatory Alternation in the Superior Temporal Gyrus of Schizophrenia - Izumi, Ryuta; Hino, Mizuki; Wada, Akira; Nagaoka, Atsuko; Kawamura, Takashi; Mori, Tsutomu; Sainouchi, Makoto; Kakita, Akiyoshi; Kasai, Kiyoto; Kunii, Yasuto; Yabe, Hirooki (Frontiers in Psychiatry, 2021)
Abstract Recent studies have lent support to the possibility that inflammation is associated with the pathology of schizophrenia. In the study of measurement of inflammatory mediators, which are markers of inflammation, elevated inflammatory cytokine levels in the brain and blood have been reported in patients with schizophrenia. Several postmortem brain studies have also reported changes in the expression of inflammatory cytokines. However, it is not clear how these elevated inflammatory cytokines interact with other inflammatory mediators, and their association with the pathology of schizophrenia. We comprehensively investigated the expression of 30 inflammatory mediators in the superior temporal gyrus (STG) of 24 patients with schizophrenia and 26 controls using a multiplex method. Overall, inflammatory mediator expression in the STG was mostly unchanged. However, the expression of interleukin (IL)1-α and interferon-gamma-inducible protein (IP)-10 was decreased [IL-1α, median (IQR), 0.51 (0.37-0.70) vs. 0.87 (0.47-1.23), p = 0.01; IP-10, 13.99 (8.00-36.64) vs. 30.29 (10.23-134.73), p = 0.05], whereas that of IFN-α was increased [2.34 (1.84-4.48) vs. 1.94 (1.39-2.36), p = 0.04] in schizophrenia, although these alterations did not remain significant after multiple testing. Clustering based on inflammatory mediator expression pattern and analysis of upstream transcription factors using pathway analysis revealed that the suppression of IL-1α and IP-10 protein expression may be induced by regulation of a common upstream pathway. Neuroinflammation is important in understanding the biology of schizophrenia. While neuroimaging has been previously used, direct observation to determine the expression of inflammatory mediators is necessary. In this study, we identified protein changes, previously unreported, using comprehensive protein analysis in STG. These results provide insight into post-inflammatory alternation in chronic schizophrenia.